Genome Sequencing Reveals a Large and Diverse Repertoire of Antimicrobial Peptides - Rezaei Javan, Reza; van Tonder, Andries J.; King, James P.; Harrold, Caroline L.; Brueggemann, Angela B. (Frontiers in Microbiology, 2018)
Competition among bacterial members of the same ecological niche is mediated by bacteriocins: antimicrobial peptides produced by bacterial species to kill other bacteria. Bacteriocins are also promising candidates for novel antimicrobials. Streptococcus pneumoniae (the ‘pneumococcus’) is a leading cause of morbidity and mortality worldwide and a frequent coloniser of the human nasopharynx. Here, 14 newly-discovered bacteriocin gene clusters were identified among >6,200 pneumococcal genomes. The molecular epidemiology of the bacteriocin clusters was investigated using a large global and historical pneumococcal dataset dating from 1916. These analyses revealed extraordinary bacteriocin diversity among pneumococci and the majority of bacteriocin clusters were also found in other streptococcal species. Genomic hotspots for the integration of different bacteriocin gene clusters were discovered. Experimentally, bacteriocin genes were transcriptionally active when the pneumococcus was under stress and when two strains were co-cultured in broth. These findings reveal much more diversity among bacterial defence mechanisms than previously appreciated, which fundamentally broaden our understanding of bacteriocins relative to intraspecies and interspecies nasopharyngeal competition and bacterial population structure.